Linear Algebra Examples

[4233][4233]
Step 1
Find the eigenvectors.
Tap for more steps...
Step 1.1
Find the eigenvalues.
Tap for more steps...
Step 1.1.1
Set up the formula to find the characteristic equation p(λ)p(λ).
p(λ)=determinant(A-λI2)p(λ)=determinant(AλI2)
Step 1.1.2
The identity matrix or unit matrix of size 22 is the 2×22×2 square matrix with ones on the main diagonal and zeros elsewhere.
[1001][1001]
Step 1.1.3
Substitute the known values into p(λ)=determinant(A-λI2)p(λ)=determinant(AλI2).
Tap for more steps...
Step 1.1.3.1
Substitute [4233][4233] for AA.
p(λ)=determinant([4233]-λI2)p(λ)=determinant([4233]λI2)
Step 1.1.3.2
Substitute [1001][1001] for I2I2.
p(λ)=determinant([4233]-λ[1001])p(λ)=determinant([4233]λ[1001])
p(λ)=determinant([4233]-λ[1001])p(λ)=determinant([4233]λ[1001])
Step 1.1.4
Simplify.
Tap for more steps...
Step 1.1.4.1
Simplify each term.
Tap for more steps...
Step 1.1.4.1.1
Multiply -λλ by each element of the matrix.
p(λ)=determinant([4233]+[-λ1-λ0-λ0-λ1])p(λ)=determinant([4233]+[λ1λ0λ0λ1])
Step 1.1.4.1.2
Simplify each element in the matrix.
Tap for more steps...
Step 1.1.4.1.2.1
Multiply -11 by 11.
p(λ)=determinant([4233]+[-λ-λ0-λ0-λ1])p(λ)=determinant([4233]+[λλ0λ0λ1])
Step 1.1.4.1.2.2
Multiply -λ0λ0.
Tap for more steps...
Step 1.1.4.1.2.2.1
Multiply 00 by -11.
p(λ)=determinant([4233]+[-λ0λ-λ0-λ1])p(λ)=determinant([4233]+[λ0λλ0λ1])
Step 1.1.4.1.2.2.2
Multiply 00 by λλ.
p(λ)=determinant([4233]+[-λ0-λ0-λ1])p(λ)=determinant([4233]+[λ0λ0λ1])
p(λ)=determinant([4233]+[-λ0-λ0-λ1])p(λ)=determinant([4233]+[λ0λ0λ1])
Step 1.1.4.1.2.3
Multiply -λ0λ0.
Tap for more steps...
Step 1.1.4.1.2.3.1
Multiply 00 by -11.
p(λ)=determinant([4233]+[-λ00λ-λ1])p(λ)=determinant([4233]+[λ00λλ1])
Step 1.1.4.1.2.3.2
Multiply 00 by λλ.
p(λ)=determinant([4233]+[-λ00-λ1])p(λ)=determinant([4233]+[λ00λ1])
p(λ)=determinant([4233]+[-λ00-λ1])p(λ)=determinant([4233]+[λ00λ1])
Step 1.1.4.1.2.4
Multiply -11 by 11.
p(λ)=determinant([4233]+[-λ00-λ])p(λ)=determinant([4233]+[λ00λ])
p(λ)=determinant([4233]+[-λ00-λ])p(λ)=determinant([4233]+[λ00λ])
p(λ)=determinant([4233]+[-λ00-λ])p(λ)=determinant([4233]+[λ00λ])
Step 1.1.4.2
Add the corresponding elements.
p(λ)=determinant[4-λ2+03+03-λ]p(λ)=determinant[4λ2+03+03λ]
Step 1.1.4.3
Simplify each element.
Tap for more steps...
Step 1.1.4.3.1
Add 22 and 00.
p(λ)=determinant[4-λ23+03-λ]p(λ)=determinant[4λ23+03λ]
Step 1.1.4.3.2
Add 33 and 00.
p(λ)=determinant[4-λ233-λ]p(λ)=determinant[4λ233λ]
p(λ)=determinant[4-λ233-λ]p(λ)=determinant[4λ233λ]
p(λ)=determinant[4-λ233-λ]p(λ)=determinant[4λ233λ]
Step 1.1.5
Find the determinant.
Tap for more steps...
Step 1.1.5.1
The determinant of a 2×22×2 matrix can be found using the formula |abcd|=ad-cbabcd=adcb.
p(λ)=(4-λ)(3-λ)-32p(λ)=(4λ)(3λ)32
Step 1.1.5.2
Simplify the determinant.
Tap for more steps...
Step 1.1.5.2.1
Simplify each term.
Tap for more steps...
Step 1.1.5.2.1.1
Expand (4-λ)(3-λ)(4λ)(3λ) using the FOIL Method.
Tap for more steps...
Step 1.1.5.2.1.1.1
Apply the distributive property.
p(λ)=4(3-λ)-λ(3-λ)-32p(λ)=4(3λ)λ(3λ)32
Step 1.1.5.2.1.1.2
Apply the distributive property.
p(λ)=43+4(-λ)-λ(3-λ)-32p(λ)=43+4(λ)λ(3λ)32
Step 1.1.5.2.1.1.3
Apply the distributive property.
p(λ)=43+4(-λ)-λ3-λ(-λ)-32p(λ)=43+4(λ)λ3λ(λ)32
p(λ)=43+4(-λ)-λ3-λ(-λ)-32p(λ)=43+4(λ)λ3λ(λ)32
Step 1.1.5.2.1.2
Simplify and combine like terms.
Tap for more steps...
Step 1.1.5.2.1.2.1
Simplify each term.
Tap for more steps...
Step 1.1.5.2.1.2.1.1
Multiply 44 by 33.
p(λ)=12+4(-λ)-λ3-λ(-λ)-32p(λ)=12+4(λ)λ3λ(λ)32
Step 1.1.5.2.1.2.1.2
Multiply -11 by 44.
p(λ)=12-4λ-λ3-λ(-λ)-32p(λ)=124λλ3λ(λ)32
Step 1.1.5.2.1.2.1.3
Multiply 33 by -11.
p(λ)=12-4λ-3λ-λ(-λ)-32p(λ)=124λ3λλ(λ)32
Step 1.1.5.2.1.2.1.4
Rewrite using the commutative property of multiplication.
p(λ)=12-4λ-3λ-1-1λλ-32p(λ)=124λ3λ11λλ32
Step 1.1.5.2.1.2.1.5
Multiply λλ by λλ by adding the exponents.
Tap for more steps...
Step 1.1.5.2.1.2.1.5.1
Move λλ.
p(λ)=12-4λ-3λ-1-1(λλ)-32p(λ)=124λ3λ11(λλ)32
Step 1.1.5.2.1.2.1.5.2
Multiply λλ by λλ.
p(λ)=12-4λ-3λ-1-1λ2-32p(λ)=124λ3λ11λ232
p(λ)=12-4λ-3λ-1-1λ2-32
Step 1.1.5.2.1.2.1.6
Multiply -1 by -1.
p(λ)=12-4λ-3λ+1λ2-32
Step 1.1.5.2.1.2.1.7
Multiply λ2 by 1.
p(λ)=12-4λ-3λ+λ2-32
p(λ)=12-4λ-3λ+λ2-32
Step 1.1.5.2.1.2.2
Subtract 3λ from -4λ.
p(λ)=12-7λ+λ2-32
p(λ)=12-7λ+λ2-32
Step 1.1.5.2.1.3
Multiply -3 by 2.
p(λ)=12-7λ+λ2-6
p(λ)=12-7λ+λ2-6
Step 1.1.5.2.2
Subtract 6 from 12.
p(λ)=-7λ+λ2+6
Step 1.1.5.2.3
Reorder -7λ and λ2.
p(λ)=λ2-7λ+6
p(λ)=λ2-7λ+6
p(λ)=λ2-7λ+6
Step 1.1.6
Set the characteristic polynomial equal to 0 to find the eigenvalues λ.
λ2-7λ+6=0
Step 1.1.7
Solve for λ.
Tap for more steps...
Step 1.1.7.1
Factor λ2-7λ+6 using the AC method.
Tap for more steps...
Step 1.1.7.1.1
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 6 and whose sum is -7.
-6,-1
Step 1.1.7.1.2
Write the factored form using these integers.
(λ-6)(λ-1)=0
(λ-6)(λ-1)=0
Step 1.1.7.2
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
λ-6=0
λ-1=0
Step 1.1.7.3
Set λ-6 equal to 0 and solve for λ.
Tap for more steps...
Step 1.1.7.3.1
Set λ-6 equal to 0.
λ-6=0
Step 1.1.7.3.2
Add 6 to both sides of the equation.
λ=6
λ=6
Step 1.1.7.4
Set λ-1 equal to 0 and solve for λ.
Tap for more steps...
Step 1.1.7.4.1
Set λ-1 equal to 0.
λ-1=0
Step 1.1.7.4.2
Add 1 to both sides of the equation.
λ=1
λ=1
Step 1.1.7.5
The final solution is all the values that make (λ-6)(λ-1)=0 true.
λ=6,1
λ=6,1
λ=6,1
Step 1.2
The eigenvector is equal to the null space of the matrix minus the eigenvalue times the identity matrix where N is the null space and I is the identity matrix.
εA=N(A-λI2)
Step 1.3
Find the eigenvector using the eigenvalue λ=6.
Tap for more steps...
Step 1.3.1
Substitute the known values into the formula.
N([4233]-6[1001])
Step 1.3.2
Simplify.
Tap for more steps...
Step 1.3.2.1
Simplify each term.
Tap for more steps...
Step 1.3.2.1.1
Multiply -6 by each element of the matrix.
[4233]+[-61-60-60-61]
Step 1.3.2.1.2
Simplify each element in the matrix.
Tap for more steps...
Step 1.3.2.1.2.1
Multiply -6 by 1.
[4233]+[-6-60-60-61]
Step 1.3.2.1.2.2
Multiply -6 by 0.
[4233]+[-60-60-61]
Step 1.3.2.1.2.3
Multiply -6 by 0.
[4233]+[-600-61]
Step 1.3.2.1.2.4
Multiply -6 by 1.
[4233]+[-600-6]
[4233]+[-600-6]
[4233]+[-600-6]
Step 1.3.2.2
Add the corresponding elements.
[4-62+03+03-6]
Step 1.3.2.3
Simplify each element.
Tap for more steps...
Step 1.3.2.3.1
Subtract 6 from 4.
[-22+03+03-6]
Step 1.3.2.3.2
Add 2 and 0.
[-223+03-6]
Step 1.3.2.3.3
Add 3 and 0.
[-2233-6]
Step 1.3.2.3.4
Subtract 6 from 3.
[-223-3]
[-223-3]
[-223-3]
Step 1.3.3
Find the null space when λ=6.
Tap for more steps...
Step 1.3.3.1
Write as an augmented matrix for Ax=0.
[-2203-30]
Step 1.3.3.2
Find the reduced row echelon form.
Tap for more steps...
Step 1.3.3.2.1
Multiply each element of R1 by -12 to make the entry at 1,1 a 1.
Tap for more steps...
Step 1.3.3.2.1.1
Multiply each element of R1 by -12 to make the entry at 1,1 a 1.
[-12-2-122-1203-30]
Step 1.3.3.2.1.2
Simplify R1.
[1-103-30]
[1-103-30]
Step 1.3.3.2.2
Perform the row operation R2=R2-3R1 to make the entry at 2,1 a 0.
Tap for more steps...
Step 1.3.3.2.2.1
Perform the row operation R2=R2-3R1 to make the entry at 2,1 a 0.
[1-103-31-3-3-10-30]
Step 1.3.3.2.2.2
Simplify R2.
[1-10000]
[1-10000]
[1-10000]
Step 1.3.3.3
Use the result matrix to declare the final solution to the system of equations.
x-y=0
0=0
Step 1.3.3.4
Write a solution vector by solving in terms of the free variables in each row.
[xy]=[yy]
Step 1.3.3.5
Write the solution as a linear combination of vectors.
[xy]=y[11]
Step 1.3.3.6
Write as a solution set.
{y[11]|yR}
Step 1.3.3.7
The solution is the set of vectors created from the free variables of the system.
{[11]}
{[11]}
{[11]}
Step 1.4
Find the eigenvector using the eigenvalue λ=1.
Tap for more steps...
Step 1.4.1
Substitute the known values into the formula.
N([4233]-[1001])
Step 1.4.2
Simplify.
Tap for more steps...
Step 1.4.2.1
Subtract the corresponding elements.
[4-12-03-03-1]
Step 1.4.2.2
Simplify each element.
Tap for more steps...
Step 1.4.2.2.1
Subtract 1 from 4.
[32-03-03-1]
Step 1.4.2.2.2
Subtract 0 from 2.
[323-03-1]
Step 1.4.2.2.3
Subtract 0 from 3.
[3233-1]
Step 1.4.2.2.4
Subtract 1 from 3.
[3232]
[3232]
[3232]
Step 1.4.3
Find the null space when λ=1.
Tap for more steps...
Step 1.4.3.1
Write as an augmented matrix for Ax=0.
[320320]
Step 1.4.3.2
Find the reduced row echelon form.
Tap for more steps...
Step 1.4.3.2.1
Multiply each element of R1 by 13 to make the entry at 1,1 a 1.
Tap for more steps...
Step 1.4.3.2.1.1
Multiply each element of R1 by 13 to make the entry at 1,1 a 1.
[332303320]
Step 1.4.3.2.1.2
Simplify R1.
[1230320]
[1230320]
Step 1.4.3.2.2
Perform the row operation R2=R2-3R1 to make the entry at 2,1 a 0.
Tap for more steps...
Step 1.4.3.2.2.1
Perform the row operation R2=R2-3R1 to make the entry at 2,1 a 0.
[12303-312-3(23)0-30]
Step 1.4.3.2.2.2
Simplify R2.
[1230000]
[1230000]
[1230000]
Step 1.4.3.3
Use the result matrix to declare the final solution to the system of equations.
x+23y=0
0=0
Step 1.4.3.4
Write a solution vector by solving in terms of the free variables in each row.
[xy]=[-2y3y]
Step 1.4.3.5
Write the solution as a linear combination of vectors.
[xy]=y[-231]
Step 1.4.3.6
Write as a solution set.
{y[-231]|yR}
Step 1.4.3.7
The solution is the set of vectors created from the free variables of the system.
{[-231]}
{[-231]}
{[-231]}
Step 1.5
The eigenspace of A is the list of the vector space for each eigenvalue.
{[11],[-231]}
{[11],[-231]}
Step 2
Define P as a matrix of the eigenvectors.
P=[1-2311]
Step 3
Find the inverse of P.
Tap for more steps...
Step 3.1
The inverse of a 2×2 matrix can be found using the formula 1ad-bc[d-b-ca] where ad-bc is the determinant.
Step 3.2
Find the determinant.
Tap for more steps...
Step 3.2.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
11--23
Step 3.2.2
Simplify the determinant.
Tap for more steps...
Step 3.2.2.1
Simplify each term.
Tap for more steps...
Step 3.2.2.1.1
Multiply 1 by 1.
1--23
Step 3.2.2.1.2
Multiply --23.
Tap for more steps...
Step 3.2.2.1.2.1
Multiply -1 by -1.
1+1(23)
Step 3.2.2.1.2.2
Multiply 23 by 1.
1+23
1+23
1+23
Step 3.2.2.2
Write 1 as a fraction with a common denominator.
33+23
Step 3.2.2.3
Combine the numerators over the common denominator.
3+23
Step 3.2.2.4
Add 3 and 2.
53
53
53
Step 3.3
Since the determinant is non-zero, the inverse exists.
Step 3.4
Substitute the known values into the formula for the inverse.
P-1=153[123-11]
Step 3.5
Multiply the numerator by the reciprocal of the denominator.
P-1=1(35)[123-11]
Step 3.6
Multiply 35 by 1.
P-1=35[123-11]
Step 3.7
Multiply 35 by each element of the matrix.
P-1=[351352335-1351]
Step 3.8
Simplify each element in the matrix.
Tap for more steps...
Step 3.8.1
Multiply 35 by 1.
P-1=[35352335-1351]
Step 3.8.2
Cancel the common factor of 3.
Tap for more steps...
Step 3.8.2.1
Cancel the common factor.
P-1=[35352335-1351]
Step 3.8.2.2
Rewrite the expression.
P-1=[3515235-1351]
P-1=[3515235-1351]
Step 3.8.3
Combine 15 and 2.
P-1=[352535-1351]
Step 3.8.4
Multiply 35-1.
Tap for more steps...
Step 3.8.4.1
Combine 35 and -1.
P-1=[35253-15351]
Step 3.8.4.2
Multiply 3 by -1.
P-1=[3525-35351]
P-1=[3525-35351]
Step 3.8.5
Move the negative in front of the fraction.
P-1=[3525-35351]
Step 3.8.6
Multiply 35 by 1.
P-1=[3525-3535]
P-1=[3525-3535]
P-1=[3525-3535]
Step 4
Use the similarity transformation to find the diagonal matrix D.
D=P-1AP
Step 5
Substitute the matrices.
[3525-3535][4233][1-2311]
Step 6
Simplify.
Tap for more steps...
Step 6.1
Multiply [3525-3535][4233].
Tap for more steps...
Step 6.1.1
Two matrices can be multiplied if and only if the number of columns in the first matrix is equal to the number of rows in the second matrix. In this case, the first matrix is 2×2 and the second matrix is 2×2.
Step 6.1.2
Multiply each row in the first matrix by each column in the second matrix.
[354+253352+253-354+353-352+353][1-2311]
Step 6.1.3
Simplify each element of the matrix by multiplying out all the expressions.
[185125-3535][1-2311]
[185125-3535][1-2311]
Step 6.2
Multiply [185125-3535][1-2311].
Tap for more steps...
Step 6.2.1
Two matrices can be multiplied if and only if the number of columns in the first matrix is equal to the number of rows in the second matrix. In this case, the first matrix is 2×2 and the second matrix is 2×2.
Step 6.2.2
Multiply each row in the first matrix by each column in the second matrix.
[1851+1251185(-23)+1251-351+351-35(-23)+351]
Step 6.2.3
Simplify each element of the matrix by multiplying out all the expressions.
[6001]
[6001]
[6001]
Enter YOUR Problem
using Amazon.Auth.AccessControlPolicy;
Mathway requires javascript and a modern browser.
 [x2  12  π  xdx ] 
AmazonPay